Design and Development of Solar Desalination Plant - Thaneissha, Marimuthu; Atnaw, Samson M.; Priyatharishini, Mardarveran; Sim, Shu Yi; Mazlin Azura, Usop; Muhammad Khairi, Md. Gapar; Siti Aishah, Rusdan; Roshahliza, M. Ramli; Shaharin, A. Sulaiman (EDP Sciences, 2017)
Direct sunlight has been utilized long back for desalination of water. The desalination process takes place in solar still. Solar still is a device that converts saline water to potable water. This process requires seawater and sunlight which are widely available on Earth. However, the current solar desalination generation capacity is generally low and has high installation cost. Hence, there is a need for the enhancement of the productivity which can be achieved through few modifications. This paper explores the challenges and opportunities of solar water desalination worldwide. It presents a comprehensive review of solar desalination technologies that have been developed in recent years which covers the economic and environmental aspects.